Complex effect of sulfur and phosphorus on the characteristics of wheel steel of KP-T brand before and after modification - Polishko, Serhii (Technology audit and production reserves, 2021)
The object of the research is KP-2 wheel steel modified by the Al-Mg-Si-Fe-C-Ca-Ti-Ce system. One of the most problematic places in the smelting of modern steel is the stability of the chemical composition due to the use of uncontrolled content of scrap, charge and standard modifiers, which are made by the fused method. To eliminate this problem, multifunctional modifiers were used during the study. This is due to the fact that the KP-2 steel modification method proposed in this article, has a number of features. In this case, the influence modifiers of multifunctional action on the installation of vacuum processing of steel on desulfurization of wheel steel KP-2, obtained under the conditions of the open joint-stock company Interpipe NTRP (Dnipro, Ukraine), was established. In particular, when treating a steel melt with multifunctional modifiers, not only a refining effect occurs, but also an increase in the stability of the chemical composition and level of mechanical characteristics of the KP-2 wheel steel. This is confirmed by the coefficients of variation and interfusion difference presented in the article (span), obtained by statistical processing of a large data set – 442 serial smeltings and 1 modified (6 wheels). Thanks to the multifunctional modification, the level of mechanical characteristics and the quality of the finished wheels really increases. Compared with similar mass-produced materials, such as FeSi, FeCa, FeMn, SiCa, the use of new multifunctional modifiers in KP-2 wheel steel provides a significant reduction in the mass fraction of sulfur than in the same metal that is processed in the traditional way. It has been established that the use of multifunctional modifiers changes the shape of non-metallic inclusions to globular and reduces their number, which also increases the level of mechanical properties of KP-2 wheel steel. The obtained coefficients of variation prove that the mechanical characteristics of KP-2 modified steel are more stable than in serial melts of the same steel. This will increase the demand and quality of these railway wheels.